Blog Marketing- An Emerging Promotional Strategy - Ram Raj, T. V. (Indian Journal of Marketing, 2006)
Whether it is raising the voice against the invasion of Iraq by United States or helping the victims of the Tsunami, blogs have changed the way of information flow. Blogs have emerged as a medium for the common man to raise his voice, to make his presence felt and to speak out. It is not the corporations who are behind the blogs but it is the common man all over the world who would have otherwise gone unnoticed, who is actively writing and reading the blogs. Though the blog revolution is still in its evolutionary stage, it has opened an avenue for people to express themselves on issues they feel concerned about. If one randomly looks at the authors of these blogs one will be surprised to see housewives, students, authors, actors all writing on one topic or the other.